Needle Recapping in Healthcare Settings, Occupational Risks and Implications for Biosafety: A Narrative Review - Sarmento, Marconi Queiroga; Lins, Etiene Pereira Duarte; Oliveira da Silva, Maria Cláudia; Coatti, Thiago Miguel De Medeiros; Gadelha de Oliveira, Carlos Eraldo; Clementino, Herlon Alberto; Santana, Ilan Hudson Gomes de; Morais de Lima, Cacilda Chaves; Batista Paiva, Monique Danyelle Emiliano; Cavalcanti, Maria de Oliveira Alves (Brazilian Journal of Implantology and Health Sciences, 2026)
Sharps injuries represent an important occupational hazard among healthcare professionals. Among these devices, hypodermic needles are frequently associated with percutaneous injuries, particularly during unsafe handling practices such as needle recapping. This study aimed to analyze the scientific evidence related to needle recapping practices and sharps injuries among healthcare workers. A narrative review of the literature was conducted using the PubMed/MEDLINE, Scopus, Web of Science, LILACS, and SciELO databases. Studies addressing occupational exposure to sharps instruments, associated risk factors, and preventive strategies in healthcare settings were included. After the screening process, 15 studies were selected for analysis. The findings indicate that needle recapping constitutes a significant risk factor for occupational injuries and is often associated with inadequate biosafety practices, heavy workload, and insufficient training of healthcare personnel. Furthermore, evidence suggests that institutional interventions, continuous biosafety education, and the adoption of safety-engineered devices can significantly reduce the incidence of sharps injuries. In conclusion, needlestick injuries remain a relevant occupational health problem in healthcare settings, highlighting the importance of strengthening preventive strategies and promoting a culture of safety within healthcare institutions.